A Study on Sway Stability Control Methods for Tractor-Trailer System Using Rear Wheel Steering - Wanki Cho; Youngsik Yoon; Seung-Han You (IEEE Access, 2024)
This paper proposes a control method for a Rear Wheel Steering (RWS) system aimed at improving both the sway stability and maneuverability of vehicles equipped with trailers. A total of three control methods were designed and their performance was compared. The first method involves controlling the yaw rate of the tractor similar to conventional lateral stability control. The second method directly controls the hitch angle, utilizing the Sliding Mode Control (SMC) method. The third method controls the yaw rate similar to the first method. However, the approach to determining the target yaw rate differs from that of the first method. Each control method consists of the same three modules: the target motion module, the controller module, and the distributor module. The performance of these control methods was validated through simulations using MATLAB/Simulink and CarSim vehicle dynamics software. Simulation results showed that while the first method improved sway stability compared to no control, it had limitations compared to other methods. The second method excelled in sway stability but compromising maneuverability, resulting in unfavorable trajectory tracking in simulations. The third method demonstrated superior performance in both sway stability and maneuverability.